The system of technology transfer strategies within the machine-building educational and production clusters - T. V. Kakatunova; S. S. Shirokov (Путеводитель предпринимателя)
The possibility of using innovation as a tool for financial recovery of machine-building enterprises was considered. A system of strategies for the transfer of technologies within the machine-building educational and production clusters was proposed. A model of end-to-end innovation management in the educational and industrial cluster was presented.